Optimal design of three-phase static var compensation system - George M.; Bakar M.B.B.A.; Basu K.P. (2023)
This manuscript is aimed to emphasize the application of synchronous detection method (SDM) to develop and design three-phase static var compensation (SVC) systems with minimal complexity. An optimal design for three-phase SVC system based on SDM is considered. The performance of the system has been compared with SVC system based on instantaneous active-reactive power theory. The paper exhibits unnecessary complexity involved in control algorithms other than SDM. 2012 IEEE.